ROLE OF SLANG IN KOREAN LANGUAGE AND ITS USE IN SPEECH - Toganova, Sh М (Journal of Oriental Studies, 2016)
The article describes the role of slang in the Korean language and its use in everyday life. Slang in Korean language is rapidly changing, renewing and often used. Despite of the fact that the most of slang words have been borrowed from English language, slang quickly adopted into the Korean everyday speech and found its place. Today the meaning of slang words is understood in a broad sense. Using theoretical and methodological approach the article addresses comprehensively the role of slang in Korean language and as well as its use.